Sialostent for Warthon’s Duct Repair in Submandibular Sialolithiasis in Pediatric Patient - Yosaphat Bayu Rosanto; Maria Goreti Widiastuti; Poerwati Soetji Rahajoe (Denta Journal Kedokteran Gigi, 2019)
Background: Sialolithiasis is disease found in the salivary glands which is marked by obstruction of salivary secretion by salivary gland stone. Submandibular gland is the highest predilection for sialolithiasis with 80% occurrence rate. The gland stones in Wharton's duct cause ductal stenosis and inflammation that causing pain. The main purpose of surgery on sialolithiasis is not only to take salivary gland stones, but the most important thing is to maintain the warthon duct as an outlet for the submandibular salivary glands. Objective: This paper explains case of sialolithiasis related to the management of Warthon’s duct repair surgery with sialostent in pediatric. Case: A 5 years-old female patient came to our hospital with a complaint of swealing in the floor of the mouth for 2 weeks that sometimes disturbing when eating. Clinical examination revealed a mobile 5 mm swealing and inflamation in the floor of the mouth in the sublingual caruncle. Ultrasoundgraphy examination results showed a picture of a very hyperechoic circle measuring 3 mm. Patient was planned for surgical removal of gland stone and Warthon’s duct repair with sialostent under general anesthesia. Case management: The suture technique for sialostent fixation is an important key to the success of this surgery, especially in children, because children often feel uncomfortable and want to remove this sialostent that appears intraorally. Result of this successful surgery is the Warthon’s duct can be maintained without relapse. Good soft tissue healing and normal salivary gland function. There was no complications in this surgical result. Sialolithectomy in combination with sialostent is a promising method for repairing the Wharthon duct. Conclusion: This method is able to correct the unfavorable curvature of the Warthon duct, prevent stenosis, and avoid sublingual caruncle closure due to inflammatory and healing processes.